Health-related quality of life in hoarding: A comparison to chronic conditions with high disease burden. (May 2022) - Nutley, Sara K.; Read, Michael; Eichenbaum, Joseph; Nosheny, Rachel L.; Weiner, Michael; Mackin, R. Scott; Mathews, Carol A.
Abstract: Hoarding disorder often results in debilitating functional impairment and may also compromise health-related quality of life (QoL). This study investigated the association between hoarding behavior and QoL relative to six highly impairing medical and psychiatric disorders in a sample of 20, 722 participants enrolled in the internet-based Brain Health Registry. Nearly 1 in 8 participants (12.2%) endorsed clinically relevant hoarding symptoms (CHS). In separate multivariable linear regression models, hoarding was more strongly associated with mental QoL than diabetes ( S t a n d a r d i z e d β = −0.21, 95% CI: [-0.22, −0.20] vs. −0.01 [-0.02, 0.0]), heart disease (−0.22 [-0.23, −0.20] vs. 0.00 [-0.02, 0.01]), chronic pain (−0.18 [-0.19, −0.16] vs. −0.12 [-0.13, −0.10]), post-traumatic stress disorder (PTSD; −0.20 [-0.22, −0.19] vs. −0.07 [-0.09, −0.06]), and substance use disorder (SUD; −0.21 [-0.23, −0.20] vs. −0.04 [-0.05, −0.03]). Similarly, CHS was more strongly negatively associated with physical QoL than diabetes (−0.11 [-0.10, −0.12] vs. −0.08 [-0.06, −0.09]), major depressive disorder (−0.09 [-0.10, −0.08] vs. −0.05 [-0.06, 0.03]), PTSD (−0.11 [-0.12, −0.10] vs. −0.08 [-0.09, −0.07]), and SUD (−0.12 [-0.13, −0.09] vs. −0.01 [-0.02, 0.00]). Higher hoarding severity was associated with reductions in both mental ( S t a n d a r d i z e d β  = −0.28, ΔR 2  = 0.08, p < 0.0001) and physical ( β  = −0.12, ΔR 2  = 0.02, p < 0.0001) QoL, though the strength of the relationship between hoarding symptoms and QoL varied with depression severity. Efforts to improve the overall QoL and well-being of those with CHS are needed. Highlights: Self-reported QoL impairment increases with the severity of hoarding symptomatology. Hoarding symptom severity is negatively associated with QoL even at low levels. Hoarding is more associated with QoL than most health conditions assessed. The association between hoarding and QoL varies with depression symptom severity.